2018
DOI: 10.4168/aair.2018.10.6.614
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Trajectory Types in Never-Smoking Adults With Asthma: Clinical Features and Inflammatory Patterns

Abstract: PurposeAsthma is a heterogeneous disease that responds to medications to varying degrees. Cluster analyses have identified several phenotypes and variables related to fixed airway obstruction; however, few longitudinal studies of lung function have been performed on adult asthmatics. We investigated clinical, demographic, and inflammatory factors related to persistent airflow limitation based on lung function trajectories over 1 year.MethodsSerial post-bronchodilator forced expiratory volume (FEV) 1% values we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
3
0
1
Order By: Relevance
“…Our second phenotype (Cluster 2) that was characterized by female dominance and early adult-onset asthma with high breathlessness and moderate symptoms, nearly normal lung function, and moderate healthcare use also closely aligns with findings from previous studies 22,26,29,[33][34][35] . This phenotype closely mirrors the phenotype identified by Dudchenko et al 36 , which was notably sensitive to weather as a trigger, while our phenotype had exercise and infections as important triggers.…”
Section: Discussionsupporting
confidence: 88%
“…Our second phenotype (Cluster 2) that was characterized by female dominance and early adult-onset asthma with high breathlessness and moderate symptoms, nearly normal lung function, and moderate healthcare use also closely aligns with findings from previous studies 22,26,29,[33][34][35] . This phenotype closely mirrors the phenotype identified by Dudchenko et al 36 , which was notably sensitive to weather as a trigger, while our phenotype had exercise and infections as important triggers.…”
Section: Discussionsupporting
confidence: 88%
“…All the 68 studies [ 8 , 9 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 …”
Section: Resultsunclassified
“…Although we are not aware of the potential mechanism explaining the double gap we found on FEV1 improvement in remittent vs non-remittent patients, it has been reported that blood and sputum eosinophilia could play a role determining lung function trajectory. Patients with a lower sputum eosinophilia, along with a more pronounced neutrophilic airway inflammation, tend to have a worse FEV1 trajectory, while those with a marked blood and sputum eosinophilia have a fast and sustained improvement in lung function ( 24 ). Moreover, we cannot also exclude that a certain degree of airway remodeling or the impact of comorbidities in non-remittent patients could have influenced the FEV1 improvement with anti IL5/IL5r therapy.…”
Section: Discussionmentioning
confidence: 99%